Efektivitas Pembelajaran Multiliterasi Terhadap Kemampuan Berpikir Kritis Siswa Sekolah Dasar Pada Materi Ekosistem - Febrina Dafit; Dea Mustika; Siti Quratul Ain (PD PGMI se Indonesia, 2018)
The purpose of this study was to examine and describe the multiliteracy learning on the critical thinking skills of elementary school students on ecosystem material. The study was conducted in the sixth grade of elementary school and began with preliminary observations and discussions with the teacher to find out whether multiliteracy learning had already been implemented or not before. The design of learning carried out is multiliteracy learning by teachers in grade 6th elementary school. Data collection techniques were observation, tests, interviews, and observation sheets. Observations were made on the learning process which includes teacher activities and student activities during the implementation of multiliteracy learning. The test was used to measure the level of students' critical thinking skills after multiliteracy learning. Question and interviews are used to assess the effectiveness of multiliteracy learning from the point of view of students and teachers. Multiliteracy learning gives multiliteracy to students' critical thinking skills, it can be seen that the average ability score of students in the experimental class is 17 while the control class is 14.71. Students who learn with multiliteracy learning provide positive responses to learning models that have influenced their critical thinking skills. Teachers who use multiliteracy learning models in the learning process also provide a positive response because they have helped in improving students' critical thinking skills and facilitate the learning process.